Estimating probabilities of default for German savings banks and credit cooperatives - Daniel Porath (Deutsche Bundesbank, 2004)
A healthy banking system is a fundamental condition for financial stability. When assessing the riskiness of the banking system, analysts often restrict their focus to large banks. This may create a distorted picture in countries like Germany with fragmented banking systems. In Germany, savings banks and cooperative banks taken together are important players in the market. However, little is known about their default risk. The reason is that these banks usually resolve financial distress within their own organisations, which means defaults are not observable from the outside. In this paper we use a new dataset which contains information about financial distress and financial strength of all German savings banks and cooperative banks. The data have been gathered by the Deutsche Bundesbank for microprudential supervision and have never before been exploited for macroprudential purposes. We use the data to identify the main risk drivers. To this end we estimate a default prediction model (hazard model). A second goal of the paper is to analyse the impact of macroeconomic information for forecasting banks' defaults. Recent findings for the USA have cast some doubt on the usefulness of macroeconomic information for banks' risk assessment. Contrary to recent literature, we find that macroeconomic information significantly improves default forecasts.
Keywords: C23; G28; G21; 330; bank failure; default probability; time-discrete hazard rate; Bankinsolvenz; Sparkasse; Kreditgenossenschaft; Schätzung; Deutschland